An Exploration of Media Work of A Convert Da'i: Specific Reference to Imam Suhaib Webb - Salinayanti, Salim (Universiti Malaya, 2018)
This study examines the roles of traditional media and social media in spreading daawah (Islamic propagation) through the media work of an American Muslim convert, Imam Suhaib Webb, who is active in doing daawah on television (traditional media) as well as on social media. This study also investigates the impact both traditional and social media have on the audience. His media work was chosen because he uses English in spreading daawah and it is essential especially to the non-Malay speaking communities in Malaysia. The data was collected through a method of observation on TV Al-Hijrah (Malaysian Islamic television) where Imam Suhaib Webb has his own segment, and on social media namely Facebook. The data were then analysed using thematic approach and the themes related to the roles of media in spreading daawah were established after the observation. The findings reveal that traditional media (television) has an important role in spreading daawah. However, it is found that social media (Facebook) has a more significant role in spreading da‘wah as social media has extensive roles and gives more impact on the audience than traditional media.